Analysis of Financial Literation Levels of Micro Enterprises in Kulon Progo District, Special Region of Yogyakarta - Ramadhan, Dadan; Setiartiti, Lilies (Program Studi Ekonomi FEB UMY, 2020)
This research is quantitative. The population of this research was all of Micro Enterprises in Kulon Progo Regency. The sample of this research were 156 micro-entrepreneurs in the Kulonprogo district. This research used a simple random sampling technique to get the data. The researcher used a questionnaire as the instrument, which tested both its validity and its reliability. The data analysis technique used in this research is the Chi-Square test. The result showed, the majority of respondents had knowledge (79,5%), and the ability of financial literacy (80,8%) was categorized in the high-level category. There was a no different level of financial literacy for the micro-entrepreneur in Kulon Progo Regency based on the gender.